Resveratrol inhibits nonalcoholic fatty liver disease in rats - Bujanda, Luis (BioMed Central, 2008)
BACKGROUND: The prevalence of nonalcoholic fatty liver disease (NAFLD) is high. NAFLD is linked to obesity, diabetes mellitus, and hypertriglyceridemia. Approximately 20% of patients with NAFLD will eventually develop cirrhosis. Our purpose was to investigate whether resveratrol decreased hepatic steatosis in an animal model of steatosis, and whether this therapeutic approach resulted in a decrease in tumor necrosis factor α (TNF-α) production, lipid peroxidation and oxidative stress. METHODS: Male Wistar CRL: Wi (Han) (225 g) rats were randomized into three groups. A control group (n = 12) was given free access to regular dry rat chow for 4 weeks. The steatosis (n = 12) and resveratrol (n = 12) groups were given free access to feed (a high carbohydrate-fat free modified diet) and water 4 days per week, and fasted for the remaining 3 days for 4 weeks. Rats in the resveratrol group were given resveratrol 10 mg daily by the oral route. All rats were killed at 4 weeks and assessed for fatty infiltration and bacterial translocation. Levels of TNF-α in serum, hepatic malondialdehyde (MDA), oxidative stress (superoxide dismutase, glutathione peroxidase, catalase and nitric oxide synthase) and biochemical parameters were measured. RESULTS: Fat deposition was decreased in the resveratrol group as compared to the steatosis group (Grade 1 vs Grade 3, P < 0.05). TNF-α and MDA levels were significantly increased in the steatosis group (TNF-α; 33.4 ± 5.2 vs 26.24 ± 3.47 pg/ml and MDA; 9.08 ± 0.8 vs 3.17 ± 1.45 μM respectively, P < 0.05). This was accompanied by increased superoxide dismutase, glutathione peroxidase and catalase and decreased nitric oxide synthase in the liver of resveratrol group significantly (P < 0.05 vs steatosis group). Bacterial translocation was not found in any of the groups. Glucose levels were decreased in the group of rats given resveratrol (P < 0.05). CONCLUSION: Resveratrol decreased NAFLD severity in rats. This effect was mediated, at least in part, by TNF-α inhibition and antioxidant activities.